Peningkatan Literasi dan Kreativitas Anak di Desa Binuang melalui Program Tematik Literasi - Fajar, Fajar; Fendrik, Muhammad; Huda, Miftahul; Fitriani, Novi Era; Agustra, Yuda; Ashfina, Syarifah Wilda Mairoza; Samosir, Adinda Hapsari Br.; Hayat, Marsya; Wijaya, Marsella Intania; Harahap, Wisnu Prayudha Havana; Zai, Oftafian; Salsabila, Vania Alda (Unri Conference Series: Community Engagement, 2025)
Students from the Thematic Literacy Community Service Program (Kuliah Kerja Nyata/KKN) of Universitas Riau in 2025 conducted literacy program activities at UPT SDN 005 Binuang Village. Literacy is a person's ability to use potential and skills to process and understand information when engaging in reading and writing activities (Ekowati et al., 2019). Through literacy skills, a person not only gains knowledge but can also use their knowledge and experience as capital for the future. The program was implemented at UPT SDN 005 Binuang Village from Monday, July 14, 2025, to Saturday, July 17, 2025. The objective was to improve the literacy of students at UPT SDN 005 Binuang Village through the Literacy Program. The method used involved designing the entire program. Activities began with read-aloud sessions and "Read Me A Book" for grade 1 and 2 students. Meanwhile, grade 3 and 4 students reviewed book content that had been read to them and participated in interactive quizzes. Grade 5 students expressed their understanding of book content through drawing activities, while grade 6 students were assigned to rewrite stories by connecting them to their personal experiences, and the program concluded with a literacy competition. The coloring competition was intended for lower grade students (grades 1-3), while the "Ranking 1" competition was participated by upper grade students (grades 4-6), with materials covering general knowledge, religious education, and culture. The results obtained showed that the program could significantly increase students' reading interest across all grade levels, develop fundamental literacy skills and comprehension appropriate to students' developmental stages, and create a positive and enjoyable learning environment. This success demonstrates that investment in quality literacy programs not only provides direct benefits to students' academic abilities but also contributes to the development of character, creativity, and thinking skills that will benefit them.